Changes in chemokine and growth factor levels may be useful biomarkers for monitoring disease severity in COVID-19 patients; a pilot study - Wolszczak-Biedrzycka, Blanka; Dorf, Justyna; Wojewódzka-Żelezniakowicz, Marzena; Żendzian-Piotrowska, Małgorzata; Dymicka-Piekarska, Violetta; Matowicka-Karna, Joanna; Maciejczyk, Mateusz (Frontiers in Immunology, 2024)
The aim of this study was to evaluate the diagnostic utility of serum levels of chemokines and growth factors (GFs) for monitoring the severity of the SARS-CoV-2 infection based on the patients' MEWS scores. The serum levels of the following proteins: MCP-1, MIP-1α, MIP-1β, RANTES, eotaxin, cutaneous T cell-attracting chemokine (CTACK), growth-regulated oncogene-alpha (GRO-α), interferon gamma-induced protein (IP-10), and MIG, and the serum levels of the following GFs: basic fibroblast growth factor (basic-FGF), hepatocyte growth factor (HGF), platelet-derived growth factor (PDGF-BB), stem cell growth factor-beta (SCGF-β), granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), macrophage colony-stimulating factor (M-CSF), stem cell factor (SCF), macrophage migration inhibitory factor (MIF), leukemia inhibitory factor (LIF), stromal cell-derived factor (SDF-1α), tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), and interferon gamma (INF-γ) were analyzed in hospitalized COVID-19 patients with the use of the Bio-Plex Pro™ Human Cytokine Screening Panel (Biorad) and the Bio-Plex Multiplex system. Results: The study demonstrated that IP-10, MIG, basic-FGF, and GM-CSF were the most useful diagnostic markers for distinguishing patients with different severity of COVID-19. Conclusions: MIG, basic-FGF and GM-CSF can be useful biomarkers for monitoring disease severity in patients with COVID-19.